Inflammatory Bowel Disease Increases the Risk of Venous Thromboembolism in Children: A Population-Based Matched Cohort Study. (27th June 2021) - Kuenzig, M Ellen; Bitton, Alain; Carroll, Matthew W; Kaplan, Gilaad G; Otley, Anthony R; Singh, Harminder; Nguyen, Geoffrey C; Griffiths, Anne M; Stukel, Therese A; Targownik, Laura E; Jones, Jennifer L; Murthy, Sanjay K; et al.
Abstract: Background and Aims: Although venous thromboembolism [VTE] is a well-known complication of inflammatory bowel disease [IBD] in adults, limited data exist on the risk in children. We report the incidence of VTE among children with and without IBD. Methods: We conducted a matched cohort study within a distributed network of population-based Canadian provincial health administrative databases. Children <16 years diagnosed with IBD were identified using validated algorithms from administrative data in Alberta, Manitoba, Nova Scotia, Ontario and Québec and compared to age- and sex-matched children without IBD. Hospitalizations for VTE within 5 years of IBD diagnosis were identified. Generalized linear mixed-effects models were used to pool province-specific incidence rates and incidence rate ratios [IRR] with 95% confidence intervals [CI]. Hazard ratios [HR] from Cox proportional hazards models were pooled with fixed-effects meta-analysis. Results: The 5-year incidence of VTE among 3593 children with IBD was 31.2 [95% CI 23.7–41.0] per 10 000 person-years [PY] compared to 0.8 [95% CI 0.4–1.7] per 10 000 PY among 16 289 children without IBD [unadjusted IRR 38.84, 95% CI 16.59–90.83; adjusted HR 22.91, 95% CI 11.50–45.63]. VTE was less common in Crohn's disease than ulcerative colitis [unadjusted IRR 0.47, 95% CI 0.27–0.83; adjusted HR 0.52, 95% CI 0.29–0.94]. The findings were similar for deep vein thrombosis and pulmonary embolism when comparing children with and without IBD. Conclusions: The risk of VTE is much higher in children with IBD than controls without IBD. While the absolute risk is low, we found a higher incidence rate than previously described in the pediatric literature. Conference Presentation: An abstract based on the data included in this paper was presented at Canadian Digestive Diseases Week [Montréal, Canada] in March 2020.